Diagnostic Imaging Management System in Batu Pahat Hospital - Abdullah, Nuraini; Selamat, Norhanim; Kasim, Shahreen (International Journal of Advanced Science Computing and Engineering, 2019)
Â Management System Development Department of Diagnostic Imaging at Hospital Batu Pahat is an effort to automate the existing manual system which includes the application of radiological, patient information storage, information storage staff, patient follow-up appointments, patient and personal property items stored equipment information manually. Storage of records in this manual will result in duplication of information if the patient came to do the x-ray followup. In addition, all patients who undergoing treatment radiological are required to leave their personal belongings outside the treatment room. This is likely the patient will lose personal items is high. The main purpose of this system to ensure the Diagnostic Imaging Department of Hospital Batu Pahat in upgrading and improving its service performance. Prototype Model development methodology used in this project. The system will help facilitate the management of daily operations of the Department of Diagnostic Imaging. As a result of this project is expected to assist the Department of Diagnostic Imaging towards more efficient management of the organization, in line with government efforts to provide the best service to the people.